'The Woman Teacher', 1931 (1931)
1931 1918-1939 "'The Woman Teacher', 1931" [EP0096], 1931 The front page for the 17 July 1931 issue of The Woman Teacher lists the objects of the National Union of Women Teachers, including equal pay. Founded in 1904 as the Equal Pay League, the Union wound up in 1961, when equal pay had been achieved.